Role of membrane cholesterol in platelet calcium signalling in response to VWF and collagen under stasis and flow - van Lier, Marjolijn; Verhoef, Sandra; Cauwenberghs, Sandra; Heemskerk, Johan W. M.; Akkerman, Jan-Willem N.; Heijnen, Harry F. G. (Thrombosis and Haemostasis, 2008)
Several studies have highlighted a specific role for membrane cholesterol domains in platelet signalling. Upon adhesion to von Willebrand factor (VWF) or collagen, cholesterol-rich domains (CRDs) accumulate in filopodial extensions and selectively harbour counterpart receptors (GPIb and GPVI) and associated signalling molecules. In the present study we have addressed the role of membrane cholesterol in Ca2+ signalling and secretion during the interaction of platelets with VWF and collagen.VWF/ ristocetin-induced platelet aggregation was delayed after treatment with methyl β-cyclodextrin (mbCD), but the maximal aggregation response was not affected. Platelet spreading but not adhesion to immobilised VWF under flow was attenuated by cholesterol removal, and accompanied by moderate lowering in the spiking Ca2+ response. On the other hand, platelet interaction with collagen was quite sensitive to cholesterol depletion. Platelet aggregation decreased after treatment with mbCD, and Ca2+ responses were decreased, both under static and flow conditions. Cholesterol depletion affected the secondary feedback activation via release of thromboxane A2 and ADP. The collagen-induced secretion of alpha granules and surface translocation of P-selectin and CD63 was also critically affected by cholesterol depletion. Confocal microscopy showed localization of p-Tyr at sites of contact with substrate and other platelets, where also CRDs accumulate. Our data thus reveal a more critical role for membrane cholesterol in collagen-induced than in VWF-induced Ca2+ signalling, and furthermore support the concept that secondary activation responses are dependent on intact CRDs.
Keywords: Collagen; von Willebrand factor; calcium; cholesterol-rich domains